PENGARUH MEDIA PEMBELAJARAN PAPAN PERKALIAN TERHADAP HASIL BELAJAR MATEMATIKA MATERI PERKALIAN DI KELAS IV SD INPRES OESAPA - Uco R. Anin; Alvin Javier Hano; Roswita Loiba Nahak (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Mathematics learning at the elementary school level still encounters various challenges, particularly in multiplication material, where students often experience difficulties in understanding abstract concepts. One of the contributing factors is the limited use of instructional media that can visualize mathematical concepts concretely. This study aimed to determine the effect of multiplication board learning media on the mathematics learning outcomes of fourth-grade students at SD Inpres Oesapa. The research employed a quantitative approach using an experimental method with a pretest–posttest design. The research subjects consisted of 28 fourth-grade students. Data were collected through achievement tests, classroom observations, and documentation. The research instrument was validated through validity and reliability testing before implementation. Data analysis included descriptive statistics, validity testing, reliability testing, normality testing, and hypothesis testing using SPSS version 25. The findings indicated that the implementation of multiplication board learning media significantly improved students' mathematics learning outcomes. The average pretest score increased from 36.25 to 83.39 in the posttest. Furthermore, students' minimum score improved from 5 to 75 after the treatment. The hypothesis test demonstrated a statistically significant effect of multiplication board learning media on mathematics learning outcomes. These findings indicate that multiplication board learning media provides meaningful learning experiences, facilitates conceptual understanding, increases student participation, and improves learning achievement. Therefore, multiplication board learning media can be recommended as an alternative instructional medium for teaching multiplication concepts in elementary schools.